Spontaneous mid-trimester rupture of a non-scarred gravid uterus - Sinha, Mridu; Raturi, Sushma; Alwadhi, Kimi (International Journal of Research in Medical Sciences, 2017)
Gravid uterine rupture is a life threatening condition for both mother and her fetus. Spontaneous rupture usually occurs in scarred uterus in late pregnancy without any myometrial contraction. But, rupture of a non-scarred gravid uterus in early pregnancy is a rare complication. Clinical signs and symptoms of rupture in early pregnancy are non-specific and should be differentiated from other causes of acute abdomen so that proper action should be taken in time to reduce maternal morbidity and mortality. Here we report a case of spontaneous mid-trimester rupture of an unscarred uterus in which prior evacuation caused weakening of myometrium that might have given way in this pregnancy.